Susceptibility of Aedes aegypti (Diptera: Culicidae) to temephos in Atlántico-Colombia - MAESTRE-S., RONALD; REY-V., GABRIELA; DE LAS SALAS-A., JORGE; VERGARA-S., CONSUELO; SANTACOLOMA-V., LILIANA; GOENAGA-O., SERGIO; CARRASQUILLA-F., MARÍA CRISTINA (Revista Colombiana de Entomología, 2009)
Dengue fever is endemic to the department of Atlántico; in 2007, there were 3,104 cases reported. The larvicide temephos has been used for the prevention and control of the disease. However, it is unknown if the selective pressure exerted on Aedes aegypti populations by this insecticide has generated resistance. The susceptibility of A. aegypti larvae to temephos was evaluated in seven municipalities and one county of the department of Atlántico between 2007 and 2008. Bioassays were performed using diagnostic doses of temephos (0.012 ppm) on third and early fourth Instar larvae of A. aegypti (F2), following a methodology recommended by the World Health Organization. Two repetitions were conducted, each one with four replicates and control. Susceptibility to temephos was registered for two sites (mortality rate 100%), four sites require verification for surveillance (mortality rates between 86 93%), and two showed resistance (mortality rates 34 45%). Significant differences were found in the mortality rates among populations (Kruskal-Wallis, P < 0.05). It is necessary to monitor the populations of this vector in the department of Atlántico to generate the baseline for susceptibility that will allow the implementation of preventive strategies and alternative control methods pertinent to each site, in order to reduce the selective pressure on larvae posed by the use of this larvicide.